WORK ENGAGEMENT AS A MEDIATOR IN THE RELATIONSHIP BETWEEN ORGANIZATIONAL JUSTICE AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Putu Dinda Mahadewi; Made Surya Putra; I Gede Riana; Ida Bagus Ketut Surya (Adisam Publisher, 2026)
The purpose of this study is to analyze the mediating role of work engagement in the relationship between organizational justice and organizational citizenship behavior (OCB). The research population consisted of all 106 employees of Blue Point Bay Villas & Spa Uluwatu, Bali, using a saturated sampling technique. Data were collected through a survey employing structured questionnaires, supported by interviews during the pre-survey stage. Data analysis was conducted using the Structural Equation Modeling–Partial Least Square (SEM-PLS) approach. The results indicate that organizational justice has a positive and significant effect on organizational citizenship behavior. Organizational justice also positively and significantly influences work engagement, while work engagement has a positive and significant effect on organizational citizenship behavior. Furthermore, the findings show that work engagement partially and complementarily mediates the effect of organizational justice on organizational citizenship behavior. The implications of this study emphasize that improving employees’ organizational citizenship behavior can be achieved by enhancing competencies, creating a positive and supportive work environment, opening communication channels to accommodate employees’ aspirations and complaints, and continuously evaluating and refining organizational policies to strengthen perceptions of fairness and job satisfaction